Long-Segment Tracheal Reconstruction With Free Radial Forearm Flap Reinforced by Rib Cartilage. Issue 5 (May 2018) - Thomet, Céline; Modarressi, Ali; Rüegg, Eva Meia; Dulguerov, Pavel; Pittet-Cuénod, Brigitte
Abstract : Abstract: Long-segment tracheal reconstruction remains a challenge. The ideal tracheal substitute should be an epithelialized tube to prevent stenosis and sufficiently rigid to maintain airflow patency. An autologous technique using a radial forearm free flap reinforced by rib cartilage has been recently described for tracheal reconstruction. We report here two cases of complex tracheal reconstruction with a modification of this technique, which consists of the creation of two independent skin paddles to allow the reconstruction of the trachea and a second adjacent defect (eg, cervical skin, esophagus). Airway patency was achieved with no stenosis, prolonged stenting, fistula, or necrosis after 26 and 44 months, respectively. We suggest that the satisfactory outcome obtained with this modified technique is a valuable option for tracheal and adjacent defect reconstruction without the need for a second flap.